Revolusi Layanan Kampus: Transformasi Digital di Era Perguruan Tinggi Modern - Ika Dama Yanti Nasution (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Digital transformation in public services at public universities requires adaptation not only from a technological perspective but also from a user experience and satisfaction perspective. This study uses a descriptive qualitative approach to in-depth explore user perceptions, experiences, and expectations of the one-stop service at the University of North Sumatra (USU) Integrated Service Unit (ULT) in 2023. Data were collected through semi-structured interviews with students and staff, direct observation of service processes at the ULT, and analysis of policy documents and user feedback. The analysis was conducted using the SERVQUAL framework, which highlights five key dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that the majority of users view the digitalization of ULT services as a positive step, facilitating access, accelerating administrative processes, and increasing transparency. Responsiveness and reliability were the most dominant factors in shaping satisfaction, particularly due to the online ticketing system and real-time notifications that expedite request processing. However, several challenges were also identified, such as limited physical facilities in the waiting room, the need for digital training for some users, and the expectation for the development of more varied self-service features. This study confirms that the success of one-stop shop transformation in higher education is determined not only by technological innovation but also by the institution's ability to holistically understand user needs and aspirations. Practical implications of this research include the need to improve digital literacy, strengthen service infrastructure, and develop sustainable feedback mechanisms to ensure inclusive, responsive, and user-oriented public services. These findings also enrich the literature on public administration in Indonesia, particularly in the context of user experience-based digital service evaluation in the post-pandemic era.